System-wide molecular dynamics of endothelial dysfunction in Gram-negative sepsis - Gallart-Palau, Xavier (2021)
Background: Inflammation affecting whole organism vascular networks plays a central role in the progression and establishment of several human diseases, including Gram-negative sepsis. Although the molecular mechanisms that control inflammation of specific vascular beds have been partially defined, knowledge lacks on the impact of these on the molecular dynamics of whole organism vascular beds. In this study, we have generated an in vivo model by coupling administration of lipopolysaccharide with stable isotope labeling in mammals to mimic vascular beds inflammation in Gram-negative sepsis and to evaluate its effects on the proteome molecular dynamics. Proteome molecular dynamics of individual vascular layers (glycocalyx (GC), endothelial cells (EC), and smooth muscle cells (SMC)) were then evaluated by coupling differential systemic decellularization in vivo with unbiased systems biology proteomics. Results: Our data confirmed the presence of sepsis-induced disruption of the glycocalyx, and we show for the first time the downregulation of essential molecular maintenance processes in endothelial cells affecting this apicalvascular coating. Similarly, a novel catabolic phenotype was identified in the newly synthesized EC proteomes that involved the impairment of protein synthesis, which affected multiple cellular mechanisms, including oxidative stress, the immune system, and exacerbated EC-specific protein turnover. In addition, several endogenous molecular protective mechanisms involving the synthesis of novel antithrombotic and anti-inflammatory proteins were also identified as active in EC. The molecular dynamics of smooth muscle cells in whole organism vascular beds revealed similar patterns of impairment as those identified in EC, although this was observed to a lesser extent. Furthermore, the dynamics of protein post translational modifications showed disease-specific phosphorylation sites in the EC proteomes. Conclusions: Together, the novel findings reported here provide a broader picture of the molecular dynamics that take place in whole organism vascular beds in Gram-negative sepsis inflammation. Similarly, the obtained data canpave the way for future therapeutic strategies aimed at intervening in specific protein synthesis mechanisms of the vascular unit during acute inflammatory processes.